Distribution of individual cytoplasmic pH values in a population of the yeast Saccharomyces cerevisiae - Cimprich, P; Slavík, J; Kotyk, A (FEMS microbiology letters, 1995)
Fluorescence ratio imaging microscopy using pH-sensitive fluorescent dyes makes it possible to evaluate statistical distribution of intracellular pH in a population of the yeast S. cerevisiae examined in a thin layer of suspension in a Petri dish. The distribution appears to fit a Gaussian curve with a half-width around the 0.4 pH unit. The curve became slightly narrower after resuspension in a strong buffer; the mean values shifted with the pH of the buffer. The shape of the distribution curves of both resting and growing cells in various phases of growth does not change significantly. Likewise, addition of 1% of glucose, 50 microM suloctidil or 100 microM diethylstilbestrol brings about no alteration. The only value which clearly changes is the average cytoplasmic pH.
Keywords: fluorescenční barviva; Saccharomyces cerevisiae; koncentrace vodíkových iontů; Fluorescent Dyes; Hydrogen-Ion Concentration; Cytoplasm; cytoplazma